Semi-structural credit gap estimation - Jan Hannes Lang; Peter Welz (European Central Bank (ECB), 2018)
This paper proposes a semi-structural approach to identifying excessive household credit developments. Using an overlapping generations model, a normative trend level for the real household credit stock is derived that depends on four fundamental economic factors: real potential GDP, the equilibrium real interest rate, the population share of the middle-aged cohort, and institutional quality. Semi-structural household credit gaps are obtained as deviations of the real household credit stock from this fundamental trend level. Estimates of these credit gaps for 12 EU countries over the past 35 years yield long credit cycles that last between 15 and 25 years with amplitudes of around 20%. The early warning properties for financial crises are superior compared to credit gaps that are obtained from purely statistical filters. The proposed semistructural household credit gaps could therefore provide useful information for the formulation of countercyclical macroprudential policy, especially because they allow for economic interpretation of observed credit developments.
Keywords: E32; E51; E21; G01; D15; 330; equilibrium credit; credit cycles; financial crises; macro-prudential analysis; early-warning models